Effect of Fertilizers, Biochar and Humic acid on Seed Yield and Nutrient content of Maize (Zea mays L.) Grown on Alfisols of Telangana - Madhavi, P.; Sailaja, V.; Prakash, T. Ram; Hussain, S. A. (International Journal of Economic Plants, 2017)
A field study was carried out at college farm, College of Agriculture, Rajendranagar, Hyderabad, Andhra Pradesh during Kharif 2013 on an Alfisol to find out most efficient combination of biochar, humic acid and inorganic sources of nutrients to increase the productivity and nutrient content of maize. Soil had a pH of 7.72, EC of 0.217 dS m-1with low organic carbon (0.49%) and available nitrogen (138.6 kg ha-1), high available phosphorus (31.28 kg ha-1) and potassium (629 kg ha-1) and sufficient available sulphur (28 ppm). The experiment was laid out in a Randomized Block Design and replicated thrice with three factors comprised of factor-I (fertilizers- 100 % RDF and 75 % RDF), Factor-II (biochar levels- 0, 5 and 7.5 t ha-1) and Factor-III (humic acid levels of 0 and 30 kg ha-1). Recommended dose of NPK along with biochar at 7.5 t ha-1and humic acid at 30 kg ha-1 was significant in increasing seed yield (60.71 q ha-1). Though in the absence of biochar, 75% NPK put forth significantly lower yield (41.22 q ha-1) than 100% NPK (52.10 q ha-1), integration with biochar at the highest level of 7.5 t ha-1 and humic acid at 30 kg ha-1, the yields from the two levels of fertilizers were at a par. Seed N content was higher in 100% NPK along with biochar @ 7.5 t ha-1 and humic acid 30 kg ha-1 (1.236 %) followed by 1.127% with 75% NPK along with biochar @ 5 t ha-1 and humic acid 30 kg ha-1. In case of P and K, highest contents of 0.500 and 0.618 % was observed with 100% NPK and humic acid 30 kg ha-1 along with biochar @ 7.5 and 5 t ha-1 respectively.